Manajemen Helpdesk dan Dukungan Teknis di Sekolah Berbasis Pembelajaran Digital - Didit Darmawan; Putri kholifatul Khasanah; Rosita Suciati; Rahayu Mardikaningsih; Nurul Ilmiyah Al Makrufah (Jurnal Al-Fatih, 2026)
Technical disruptions in technology-enhanced schools frequently interrupt lessons and diminish user confidence. This study aims to design a helpdesk management model as a systematic solution to support the continuity of digital learning. Using a qualitative literature review, this study synthesizes organizational management principles to develop an effective technical support framework. The findings identify four pillars of helpdesk management: a clear team structure, structured incident reporting procedures, defined response time standards, and self-directed troubleshooting training for teachers and students. Successful implementation relies on transparent communication, systematic case documentation, and the formal recognition of the helpdesk unit within the school organization. The main contribution of this research is an integrated framework that transforms technical support from incidental tasks into a structured management system that bolsters pedagogical innovation. This model provides practical guidance for school leaders to plan and evaluate technical services to maintain stable digital learning environments.